FARG‘ONA VODIYSIDA TARQALGAN ITSIMONLAR PARAZITI TOXOCARA CANIS NEMATODASINING MORFOLOGIYASI VA BIOLOGIYASI - Sotiboldiyev Akbarxon G‘aybullo o‘g‘li, Sotiboldiyev Akbarxon G‘aybullo o‘g‘li (Actual problems and prospects of the study of the fauna, 2024)
The article presents studies on the distribution, morphology and biology of the nematode Toxocara canis, parasitizing wild and domestic dogs, in the Fergana Valley. According to the results of the studies, the morphological structure and morphometric dimensions of the species T. canis correspond to the indicators given in the literature. This information can also be used to develop recommendations for the prevention and control of this disease.